2013
DOI: 10.1007/s10529-013-1434-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of bile salt hydrolase genes from Lactobacillus plantarum CGMCC No. 8198

Abstract: Genes coding for bile salt hydrolase of Lactobacillus plantarum CGMCC 8198, a novel probiotic strain isolated from silage, were identified, analyzed and cloned. L. plantarum strongly resisted the inhibitory effects of bile salts and also decreased serum cholesterol levels by 20% in mice with hypercholesterolemia. Using RT-PCR analysis, bsh2, bsh3 and bsh4 were upregulated by bile salts in a dose-dependent manner. All three bsh genes had high similarity with those of other Lactobacillus strains. All three recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Kumar et al (2013) studied the characteristics of recombinant (r) BSH of L. fermentum NCDO394 and identified that purified rBSH enzyme hydrolyzed six major bile substrates, with a special preference toward glycine-conjugated bile salts and exhibited maximal activity against GCA. Previous studies also confirmed that BSHs from Lactobacillus spp., including L. salivarius (Wang et al, 2012), L. plantarum CGMCC 8198 (Gu et al, 2014), and BSH-C of L. johnsonii PF01 (Chae et al, 2013), had a substrate specificity toward glyco-conjugated bile salts. Biochemical characterization studies revealed that the pH and temperature optima of Lg BSH were, respectively, found to be 5.5 and 52°C.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al (2013) studied the characteristics of recombinant (r) BSH of L. fermentum NCDO394 and identified that purified rBSH enzyme hydrolyzed six major bile substrates, with a special preference toward glycine-conjugated bile salts and exhibited maximal activity against GCA. Previous studies also confirmed that BSHs from Lactobacillus spp., including L. salivarius (Wang et al, 2012), L. plantarum CGMCC 8198 (Gu et al, 2014), and BSH-C of L. johnsonii PF01 (Chae et al, 2013), had a substrate specificity toward glyco-conjugated bile salts. Biochemical characterization studies revealed that the pH and temperature optima of Lg BSH were, respectively, found to be 5.5 and 52°C.…”
Section: Discussionmentioning
confidence: 99%
“…BSH deconjugation activity is well represented among intestinal microbial genera 10,22 , it is predominantly characterized among gram-positive species Bifidobacterium [23][24][25] , Clostridium 26,27 , Enterococcus 28,29 , Listeria 30 , and Lactobacillus [31][32][33][34][35][36][37][38] , including Lb. plantarum species [39][40][41][42][43] . In addition, several investigators reported that bile tolerance is a strain-specific trait and tolerances of species cannot be generalized within a species or a genus 15,16 .…”
mentioning
confidence: 99%
“…The intricate interconnection of the genera Lactobacillus [102][103][104][105][106] Enterococcus [107,108], Bifidobacterium [109,110], Clostridium [111], Bacteroides [112], Peptostreptococcus [113] regulates primary bile salt synthesis and secondary bile salt metabolism of the host [114]. Growth-promoting mechanism of most subtherapeutic dose antibiotics can be related to decreased activity of the bile salt hydrolase (BSH) enzyme that catalyses deconjugation of bile salts [115].…”
Section: Discussionmentioning
confidence: 99%